From the Pictorial Turn to the Embodiment of Vision - Palatinus, David Levente (American & British Studies Annual, 2010)
The purpose of this paper is to map out the semiotic, cultural-historical and ideological discourses that constitute the theoretical framework of the study of visual culture, and to anchor the problem of response in an underlying phenomenology of perception. The article argues that the strong cognitive-emotional responses that images generate are indicative of the corporeal conditioning of aesthetics, which places the entirety of visual discourse into an anthropological perspective.